1990
DOI: 10.1099/00221287-136-10-2043
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and fatty acid composition of freshwater cyanobacteria

Abstract: Four species of freshwater cyanobacteria (A&M cyZidricu, Anucystis n&Zans, Nostoc canilta and Nostoc muscorum) contained as major lipid classes monogalactosyldiacylglycerols, digalactosyldiacylglycerols, sulphoquinovosyldiacylglycerols and phosphatidylglycerols. Unlike photosynthetic eukaryotes, cyanobacteria incubated for 7 d in the dark suffered no decrease in the concentrations of these classes, except for N. museorum. Growth, photosynthesis and nitrogen fixation were 3040% lower after dark incubation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Terminally branched fatty acids (i15:0 and a15:0) were attributed to heterotrophic bacteria as they are not commonly found in cyanobacteria (Parker et al, 1967;Merritt et al, 1991;Ahlgren et al, 1992). Due to its high concentration in many freshwater cyanobacteria (Sallal et al, 1990;Merritt et al, 1991;Ahlgren et al, 1992), PLFA 16:1x7 was used to track changes in the contribution of cyanobacteria. The relative abundance of these diagnostic PLFA can vary among microbial grouping given that relative phospholipid content varies among microbial groups (e.g., White, 1983;Cooksey et al, 1987;Findlay et al, 1989).…”
Section: Phospholipid Fatty Acid Analysismentioning
confidence: 99%
“…Terminally branched fatty acids (i15:0 and a15:0) were attributed to heterotrophic bacteria as they are not commonly found in cyanobacteria (Parker et al, 1967;Merritt et al, 1991;Ahlgren et al, 1992). Due to its high concentration in many freshwater cyanobacteria (Sallal et al, 1990;Merritt et al, 1991;Ahlgren et al, 1992), PLFA 16:1x7 was used to track changes in the contribution of cyanobacteria. The relative abundance of these diagnostic PLFA can vary among microbial grouping given that relative phospholipid content varies among microbial groups (e.g., White, 1983;Cooksey et al, 1987;Findlay et al, 1989).…”
Section: Phospholipid Fatty Acid Analysismentioning
confidence: 99%
“…Cyanobacteria also synthesize lipids (LP) that are mainly composed of diacylglycerols (Sallal et al . ; Sheng et al . ) and can be transformed to biodiesel (Sheng et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although there seems to be a tight correlation between SQDG and phototropic organisms, which implies that SQDG might play an important role for photosynthesis, the presence of SQDG does not always correlate with photosynthetic ability. Thus, some phototrophic bacteria lack or possess only small amounts of SQDG (Sallal et al ., 1990; Merritt et al ., 1991) while non‐photosynthetic organisms like Rhizobium meliloti and the extreme thermoacidophilic Alicyclobacillus acidocaldarius (Wisotzkey et al ., 1992) possesses SQDG (Langworthy et al ., 1976; Cedergreen and Hollingsworth, 1994). Deletion studies revealed that SQDG is important only under certain conditions such as phosphate limitation (Benning et al ., 1993); furthermore, it was recently demonstrated that the UDP‐sulfoquinovose synthase was upregulated under salt stress conditions, implying a important role for maintaining the integrity and stability of the thylakoid membrane under these stress conditions (Xu et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%